2017
DOI: 10.5194/acp-17-15293-2017
|View full text |Cite
|
Sign up to set email alerts
|

Emission factors of black carbon and co-pollutants from diesel vehicles in Mexico City

Abstract: Abstract. Diesel-powered vehicles are intensively used in urban areas for transporting goods and people but can substantially contribute to high emissions of black carbon (BC), organic carbon (OC), and other gaseous pollutants. Strategies aimed at controlling mobile emissions sources thus have the potential to improve air quality and help mitigate the impacts of air pollutants on climate, ecosystems, and human health. However, in developing countries there are limited data on the BC and OC emission characteris… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…7b, the relative contributions of kilometres driven by Swedish Euro 0 to Euro VI HDTs are shown. Zhang et al (2014) reported no statistically significant difference in fuel consumption among Euro II to Euro IV buses under a real-world typical bus driving cycle in Beijing. In this study, we assume the fuel consumption per kilometre and fuel density are the same across the different Euro class HDTs, and, adopting the average fuel-based EFs calculated in this study (Tables 1 and 2), the approximations of contributions of pollutants emitted from Swedish HDTs in each Euro class to the total PM, PN, BC, and NO x emissions are depicted in Fig.…”
Section: Fleet Characteristicsmentioning
confidence: 93%
“…7b, the relative contributions of kilometres driven by Swedish Euro 0 to Euro VI HDTs are shown. Zhang et al (2014) reported no statistically significant difference in fuel consumption among Euro II to Euro IV buses under a real-world typical bus driving cycle in Beijing. In this study, we assume the fuel consumption per kilometre and fuel density are the same across the different Euro class HDTs, and, adopting the average fuel-based EFs calculated in this study (Tables 1 and 2), the approximations of contributions of pollutants emitted from Swedish HDTs in each Euro class to the total PM, PN, BC, and NO x emissions are depicted in Fig.…”
Section: Fleet Characteristicsmentioning
confidence: 93%
“…NOx (NO + NO2) emission factors from the charcoal supply chain are highest from its use and transport (Akagi et al, 2011;Zavala et al, 2017), predominantly (90%) emitted as NO (Arashidani et al, 1996). NOx has both direct and indirect effects on health.…”
Section: The Charcoal Supply Chain In Africamentioning
confidence: 99%
“…Total NMVOCs emissions (Table 3.3) were partitioned into individual chemical components based on source profiles from Akagi et al (2011) for charcoal and production and use and from (Zavala et al, 2017) for trucks. In this research, individual NMVOC species partitioned for charcoal production and use are: ethylene, ethane, methanol, formaldehyde, acetic acid, and formic acid.…”
Section: Assessing Air Quality and Climate Impact Of The Charcoal Industry In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, traditional brick production is a serious local health hazard to the residents of the poor neighborhoods that typically host brickyards, as well as to brickmakers themselves. Impacts of toxic emissions on brick producers' respiratory health and the environment have been documented in a number of studies (e.g., Zuskin et al, 1998;Co et al, 2009;Martínez-Salinas et al, 2010;Kaushik et al, 2012). Although production zones are clustered at the periphery of -or even within -urban areas, laborers and their families often lack access to adequate public services including clean water, basic sanitation facilities, health services, trans-port, and education infrastructure.…”
Section: Introductionmentioning
confidence: 99%